(untitled) (AYUSHDHARA, 2022)
In present era burden of lifestyle disorders are rapidly increasing worldwide. Modernization, development of science and technology lead to more sedentary life style. Obesity or overweight (Sthoulya) is one among the major lifestyle disorder which disturbs physical, mental and social health of an individual. Obesity represents a state of excessive accumulation of body fat. Although similar, the term overweight is defined as an excess of body weight for height. In Ayurveda obesity is described as Sthoulya, which is mentioned under Santarpanajnaya Vyadhi. Ayurveda has comprehensive approach for Sthoulya. Acharya Charaka has prescribed Apatarpana Chikitsa. Panchakarma by its Virechana therapy effect is intended for purification of the body by which the accumulated morbid Doshas expelled out and produces in ideal environment for functioning of body. Present single case study showed important role of Panchakarma specifically Virechana Karma in the management of Sthoulya, by detoxification to reduce Kapha -Meda from the body and prevents its complications. The Chikitsa adopted was Deepana- Pachana, Shodhananga Snehapana with Murchita Tila Taila followed by Virechana Karma with Trivrit lehya. After completion of Samsarjana Karma it has shown significant result in reducing weight about 7 kilograms and reducing the signs and symptoms of Sthoulya. Thus, Ayurvedic line of management gives satisfactory results as well as equally beneficial for the promotion and prevention of health in Obesity.